2016
DOI: 10.1038/nbt.3714
|View full text |Cite
|
Sign up to set email alerts
|

MRI measurements of reporter-mediated increases in transmembrane water exchange enable detection of a gene reporter

Abstract: Non-invasive imaging of gene expression can be used to track implanted cells in vivo but often requires the addition of an exogenous contrast agent that may have limited tissue access1. We show that the urea transporter (UT-B) can be used as a gene reporter, where reporter expression was detected using 1H MRI measurements of UT-B-mediated increases in plasma membrane water exchange. HEK cells transfected with the reporter showed an increased apparent water exchange rate (AXR), which increased in line with UT-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 29 publications
0
60
0
Order By: Relevance
“…3C). Together with another water channel published shortly after this work *[33], aquaporin represents a new category of MRI reporter genes that is sensitive, compact, autologous to its host, nonmetallic and non-toxic.…”
Section: Calling Nature’s Plumber: Water Channels As Reporter Genes Fmentioning
confidence: 99%
“…3C). Together with another water channel published shortly after this work *[33], aquaporin represents a new category of MRI reporter genes that is sensitive, compact, autologous to its host, nonmetallic and non-toxic.…”
Section: Calling Nature’s Plumber: Water Channels As Reporter Genes Fmentioning
confidence: 99%
“…In light of the importance of transmembrane diffusion, it was recently proposed that facilitating water exchange across the membrane by overexpressing water-permeable channels would result in enhanced contrast in DWI or more specialized sequences [56, 57]. The most natural class of molecules for achieving this goal is aquaporins, a highly conserved family of tetrameric integral membrane proteins that mediate the selective exchange of water molecules across the plasma membrane in a wide range of cell types [5863].…”
Section: Emerging Mechanisms Of Biomolecular Mri: Diffusion Hypermentioning
confidence: 99%
“…In addition to aquaporin, a separate study recently reported that the urea transporter (UT-B) could also be used as a reporter gene based on its ability to increase the permeability of cell membranes [57]. In addition to urea, UT-B is able to transport water at rates similar to aquaporin.…”
Section: Emerging Mechanisms Of Biomolecular Mri: Diffusion Hypermentioning
confidence: 99%
“…Pioneering examples include enzymes that alter the relaxivity of gadolinium chelates 39 , human iron storage and transport genes such as ferritin 40, 41 and transferrin 42 , and natural and engineered proteins with large numbers of chemically labile protons for chemical exchange saturation transfer (CEST) imaging 4348 . Recent developments have also included reporter genes causing accumulation of MRI-detectable compounds 49 , proteins interacting with hyperpolarized molecules 50, 51 , channels that alter the diffusion of water across cell membranes 52, 53 and vasodilators altering hemodynamic signals 54 . Several of these reporter genes are covered in detail in previous review articles 5557 .…”
Section: Main Textmentioning
confidence: 99%